Unveiling the Scented Symphony: Exploring Lemongrass (Cymbopogon Citratus) Essential Oil's Influence on Brain Waves Through Quantitative Electroencephalogram: Lemongrass essential oil and brain waves - Jahan, Israt; Sadia, Esaba; Ferdousi, Sultana (Journal of the Medical College for Women & Hospital, 2024)
Background: This study explores the captivating query about how olfactory stimulation affects neural activity, particularly examining changes in the absolute and relative power of lower frequency waves (delta and theta across various brain regions). This investigation employs Quantitative Electroencephalogram (QEEG) to analyze the effects of exposure to the aroma of lemongrass (Cymbopogon Citratus) essential oil. Aim: To evaluate the impact of inhaling lemongrass (Cymbopogon Citratus) essential oil aroma on EEG patterns in awake healthy female adults, employing power spectral analysis. Materials and Method: In this self-controlled experiment, 30 healthy adult female participants were exposed to the water mist as control and after taking baseline recording, they inhaled aromatic mist from room air, and again brain activities were recorded using QEEG. Data was collected from scalp electrodes readings and outcomes from before and after exposure to the aroma were compared. This analysis was strengthened by comparing the results between exposure to water mist and oil mist employing the Wilcoxon Matched-Pairs Signed Rank Test. Results: Significant elevation of absolute and relative power of theta in prefrontal region (p=0.002; p=0.000) along with rise of delta and theta absolute power in frontal area (p=0.000; p=0.000) was observed. Conclusion: This study sheds light onto the background oscillatory fluctuations in lower frequency bands that may indicate more relaxed state of brain activity due to inhalation of lemongrass essential oil. J Med Coll Women Hosp.2024; 20 (1):16-22